Senescent human melanocytes drive skin ageing via paracrine telomere dysfunction. (21st October 2019) - Victorelli, Stella; Lagnado, Anthony; Halim, Jessica; Moore, Will; Talbot, Duncan; Barrett, Karen; Chapman, James; Birch, Jodie; Ogrodnik, Mikolaj; Meves, Alexander; Pawlikowski, Jeff S; Jurk, Diana; et al.
Abstract: Cellular senescence has been shown to contribute to skin ageing. However, the role of melanocytes in the process is understudied. Our data show that melanocytes are the only epidermal cell type to express the senescence marker p16 INK4A during human skin ageing. Aged melanocytes also display additional markers of senescence such as reduced HMGB1 and dysfunctional telomeres, without detectable telomere shortening. Additionally, senescent melanocyte SASP induces telomere dysfunction in paracrine manner and limits proliferation of surrounding cells via activation of CXCR3‐dependent mitochondrial ROS. Finally, senescent melanocytes impair basal keratinocyte proliferation and contribute to epidermal atrophy in vitro using 3D human epidermal equivalents. Crucially, clearance of senescent melanocytes using the senolytic drug ABT737 or treatment with mitochondria‐targeted antioxidant MitoQ suppressed this effect. In conclusion, our study provides proof‐of‐concept evidence that senescent melanocytes affect keratinocyte function and act as drivers of human skin ageing. Synopsis: Cellular senescence accelerates ageing of the human epidermis, but the contribution of specific cell types, in particular melanocytes to this process remains poorly understood. Here, senescent melanocytes are shown to affect keratinocyte function and cause ageing‐associated skin thinning, offering potential therapeutic opportunities to alleviate tissue decline. Senescent p16 INK4 ‐positive melanocytes accumulate in human skin with age. Senescent melanocytes induce telomere damage and senescence in surrounding cells in paracrine manner. Paracrine induction of telomere dysfunction is mediated by CXCR3 activation and increased ROS production in bystander cells. Clearance of senescent melanocytes with a senolytic drug or ROS scavengers rescues epidermal atrophy in vitro using 3D human epidermal equivalents. Abstract : Senescence in melanocytes of the ageing epidermis induces telomere damage and reduced proliferation of surrounding cells, which can be rescued by a senolytic drug.